Catalogue and Systematics of Pliensbachian, Toarcian and Aalenian Radiolarian Genera and Species - Carter, Elizabeth S. (ZRC SAZU, Založba ZRC, 2006)
This volume comprises a catalogue of 90 genera, 274 species and 13 subspecies of Pliensbachian, Toarcian and Aalenian Radiolaria. Two genera, 37 species and 3 subspecies are new formal descriptions, 24 species are described in open nomenclature. Each taxon is presented with a complete and up-to-date synonymy, original description and original remarks (translated into English where necessary), subsequent emendations, remarks by the authors of this catalogue, and etymology. Descriptions of species/subspecies further contain the original measurements, type locality, and data on geographic distribution. Plates illustrate the holotype and one or several specimens from our material, from different paleogeographic realms where possible. The material was collected from 30 measured sections in the Circum-Pacific belt (Baja California Peninsula, Oregon, British Columbia, Japan) and the Tethyan realm (Oman, Turkey, Slovenia, Austria). Abbreviated locality information and a list of all treated taxa are given in the last two chapters.A useful book for paleontologists interested in taxonomy of Jurassic radiolarians.